Desperately Seeking Structures; Or, the Futility of Form without Content - Williamson, Margaret Holmes; Wagner, Roy (Anthropologica, 2022)
A recent discussion of Kwoma asymmetric affinal exchanges (especially those concluding funerals) argues that their importance is such that affinal alliances are created solely in order to bring about such exchanges, a position that evidence from the Daribi and the Chimbu (where asymmetric affinal exchange is also the rule) seems to support; and that only in terms of such concepts as "asymmetry" and "affine" can these customs be explained. The present paper argues to the contrary that these exchanges are more usefully seen as a local expression of social relations — specifically, that affinity is less important than siblingship in the cases considered; and that abstract terms, stripped of their local reference, are without explanatory power.